EXPRESSIONS OF FUTURE IN CLASSICAL AND MODERN NEW PERSIAN - Jahani, Carina (Aspects of Iranian Linguistics, 2008)
As in several other Indo-European languages, there are two main strategies for marking future time reference in Persian:1. lexical or contextual means of expressing the future with the verb in the non-past tense2. periphrastic verbal constructions with an ‘upgraded,’ i.e. ‘pragmaticallystrengthened’ and ‘semantically bleached’ verb of volition as the auxiliary.The purpose of the paper is to make a detailed investigation of strategies employed formarking future time reference in written New Persian, both in its classical and modern variety. In Modern New Persian factual prose and fiction are described as two different varieties, since they show a considerable amount of divergence. This study does not include spoken Persian.The results show that the primary strategy for Persian when it comes to expressing future time reference is lexical/contextual marking with the non-past form of the verb. In written language, it is the one encountered the most commonly in Classical Persian (with a Ø-marked verb form) and in the fiction genre of Modern Persian (with a mi-marked verb form). The periphrastic constructions used in Persian are based on the verb ‘towant’, thus volitional constructions.